MOTION STABILITY ANALYSIS OF FOUR ROTOR AIRCRAFT BASED ON LYAPUNOV INDEX METHOD - TANG MingJun; SUN Shuai (Jixie qiangdu)
According to the four rotor aircraft in a relatively complex near earth space, easily disturbed, and the emergence of jitter and out of control of motion stability, this paper investigated the motion stability of four rotor aircraft based on Lyapunov exponents method. First of all, the dynamics model of aircraft was established by Euler Poincare equation, and then the quantitative relationship between the structure parameters and the stability of the system were analyzed. Secondly, the stability analysis was carried out by Lyapunov exponential analysis. The Lyapunov exponent was calculated and the main parameters affecting the Lyapunov exponent were analyzed. The Lyapunov exponent spectrum of the corresponding attitude of the aircraft in the taking off and landing phases was calculated, The results showed that the stability of the taking off phase was better than that of the landing stage. Finally, in view of the poor stability of the four rotor aircraft during landing phase, the motion stability of the aircraft can be improved by changing the L value of the center distance of the rotor and the body.